ANALISA PERANGKAT HUMIDIFIER PADA VENTILATOR - Sihotang, Anggi Tutamana; Priyulida, Fitria; Abdillah, Khairil; Ulina, Sri (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2023)
This study aims to analyze humidifiers on ventilators for patients. Can find out the analysis of humidifiers on ventilators, explain, and apply knowledge about analysis of humidifiers on ventilators. In this study, quantitative descriptive research types are combined with observational research methods.. There are two types of humidifiers, namely passive humidifiers and active humidifiers. With these two types of humidifiers, it's done. Measurement of ventilator performance using a passive humidifier and measurement of ventilator performance using an active humidifier on patient objects. From the measurement results of the two types of humidifiers, you can see monitor displays of flow rate, breathing frequency, oxygen saturation and breathing patterns.